A low-cost method for estimating energy expenditure during soccer refereeing - Ardigò, L. P.; Padulo, J.; Zuliani, A.; Capelli, C. (Journal of Sports Sciences, 2015)
This study aimed to apply a validated bioenergetics model of sprint running to recordings obtained from commercial basic high-sensitivity global positioning system receivers to estimate energy expenditure and physical activity variables during soccer refereeing. We studied five Italian fifth division referees during 20 official matches while carrying the receivers. By applying the model to the recorded speed and acceleration data, we calculated energy consumption during activity, mass-normalised total energy consumption, total distance, metabolically equivalent distance and their ratio over the entire match and the two halves. Main results were as follows: (match) energy consumption = 4729 ± 608 kJ, mass normalised total energy consumption = 74 ± 8 kJ/kg, total distance = 13,112 ± 1225 m, metabolically equivalent distance = 13,788 ± 1151 m and metabolically equivalent/total distance = 1.05 ± 0.05. By using a very low-cost device, it is possible to estimate the energy expenditure of soccer refereeing. The provided predicting mass-normalised total energy consumption versus total distance equation can supply information about soccer refereeing energy demand.